Using a mobile app comprising neurofeedback-based meditation and binaural beat music to treat PTSD symptoms: A qualitative analysis - Yun-Jung Choi; Na-Rae Lee (Digital Health)
Background There is a significant need for an effective and convenient symptom management and healing program for people experiencing post-traumatic stress disorder (PTSD) symptoms; however, research on this topic is lacking. Objective This study explored the experiences of individuals with PTSD who used a mobile traumatic stress management app with neurofeedback-based meditation and binaural beat music to promote their psychological recovery. Methods This study used a qualitative research method to explore the experiences of neurofeedback-based meditation and binaural beat music using a mobile traumatic stress management app to promote the psychological recovery of people experiencing chronic traumatic stress. The research question was “What is the experience of neurofeedback-based meditation and binaural beat music using the mobile traumatic stress management app?” Results The thematic content analysis of in-depth interviews held with nine participants derived 26 codes, eight sub-categories, three categories, and one theme (“Holding hope for healing from agony of mind and body”). Conclusion Neurofeedback-based meditation and binaural beat music using a mobile app helped people with PTSD symptoms to truly understand the symptoms caused by traumatic stress. Continued use of this program provides the participants with physical and psychological stability; it instills them with faith and hope.